2016
DOI: 10.1007/s00330-016-4348-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of pneumatosis intestinalis – correlation of MDCT-findings with treatment and outcome

Abstract: ObjectivesTo evaluate the clinical significance of pneumatosis intestinalis (PI) including the influence on treatment and outcome.Method and MaterialsTwo radiologists jointly reviewed MDCT-examinations of 149 consecutive emergency patients (53 women, mean age 64, range 21-95) with PI of the stomach (n = 4), small (n = 68) and/or large bowel (n = 96). PI extension, distribution and possibly associated porto-mesenteric venous gas (PMVG) were correlated with other MDCT-findings, risk factors, clinical management,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 32 publications
3
36
1
9
Order By: Relevance
“…In the present case, there was no indication for surgery because there were no signs of intestinal perforation, ischemia, or obstruction. It has been suggested that the WBC is significantly correlated with ischemia complicating PCI [4]. The WBC was within the normal range in the present patient.…”
Section: Discussionsupporting
confidence: 66%
“…In the present case, there was no indication for surgery because there were no signs of intestinal perforation, ischemia, or obstruction. It has been suggested that the WBC is significantly correlated with ischemia complicating PCI [4]. The WBC was within the normal range in the present patient.…”
Section: Discussionsupporting
confidence: 66%
“…Causas no isquémicas: obstrucción intestinal, íleo paralítico, ulcera gástrica perforada, carcinomas (colon), trauma abdominal, descompresión hiperbárica, procesos inflamatorios intraabdominales (enfermedad de Crohn, colitis ulcerativa, apendicitis, diverticulitis, pancreatitis, ingestión de cáusticos), entidades infecciosas intraabdominales (colangitis, pileflebitis, abscesos, tuberculosis e infección por Clostridium difficile), enfermedades autoinmunes (esclerodermia, lupus eritematoso sistémico, dermatomiositis, sarcoidosis), procedimientos quirúrgicos abdominales y medicamentos (esteroides, quimioterapia, inhibidores de la α-glucosidasa). Causas iatrogénicas: procedimientos endoscópicos, colangiopancreatografía endoscópica retrograda, estudios baritados, sondas de nutrición enteral 2,4,5,7,8 .…”
Section: Signos Radiológicos -Abdomenunclassified
“…La isquemia intestinal aguda, es la causa más importante de PA y/o NI, con peor pronóstico y mortalidades descritas hasta del 80-90% 3,5,7,8,9 . La probabilidad de isquemia intestinal aumenta significativamente cuando la NI se acompaña de aire en el sistema venoso portomesentérico 5 . La presencia de PA se consideraba previamente como signo de necrosis intestinal que justificaba la necesidad de cirugía urgente 8 .…”
Section: Signos Radiológicos -Abdomenunclassified
See 2 more Smart Citations